It could happen to you [videorecording (DVD)] - Anderson, Jane, 1954-; Cage, Nicolas, 1965-; Fonda, Bridget; Perez, Rosie; Pierce, Wendell; Hayes, Isaac; Cassel, Seymour, 1935-2019; Tucci, Stanley; Freeman, J. E.; Jenkins, Richard, 1947-; Buttons, Red, 1919-2006 (Columbia TriStar Home Video, 1998)
"Charlie Lang is a neighborhood cop with a heart of gold - and a money-hungry wife Muriel who's always looking for a way to cash in. When she asks Charlie to buy a Lottery ticket, he agrees, then impulsively promises half the winnings to a waitress, Yvonne. When their numbers hit, the real fun begins, as Muriel learns to live large while Charlie and Yvonne learn to love again."--Container